Atomically Dispersed Electron Traps in Cu Doped BiOBr Boosting CO2 Reduction to Methanol by Pure H2O. Issue 14 (17th January 2023) - Wang, Ke; Cheng, Ming; Xia, Fanjie; Cao, Ning; Zhang, Fanxing; Ni, Wenkang; Yue, Xuanyu; Yan, Keping; He, Yi; Shi, Yao; Dai, Wenxin; Xie, Pengfei
Abstract: Overall photocatalytic conversion of CO2 and pure H2 O driven by solar irradiation into methanol provides a sustainable approach for extraterrestrial synthesis. However, few photocatalysts exhibit efficient production of CH3 OH. Here, BiOBr nanosheets supporting atomic Cu catalysts for CO2 reduction are reported. The investigation of charge dynamics demonstrates a strong built‐in electric field established by isolated Cu sites as electron traps to facilitate charge transfer and stabilize charge carriers. As result, the catalysts exhibit a substantially high catalytic performance with methanol productivity of 627.66 µmol gcatal −1 h −1 and selectivity of ≈90% with an apparent quantum efficiency of 12.23%. Mechanism studies reveal that the high selectivity of methanol can be ascribed to energy‐favorable hydrogenation of *CO intermediate giving rise to *CHO. The unfavorable adsorption on Cu1 @BiOBr prevents methanol from being oxidized by photogenerated holes. This work highlights the great potential of single‐atom photocatalysts in chemical transformation and energy storage reactions. Abstract : The unique isolated Cu doped in BiOBr nanosheets establish a strong internal electric field, which stabilizes copper as atomically dispersed electron traps, accelerated charge transfer rate, and long‐lived charge carriers. As a result, Cu1 @BiOBr has demonstrated an unprecedent productivity of CH3 OH as 627.66 µmol gcatal −1 h −1 with selectivity near 90%.